Design of Lamivudine Loaded Metal Organic Frameworks MIL 100 (Fe) by Microwave Assisted Chemistry - Sucharitha, Palagati; Reddy, Ramesh; Jahnavi, Irivichetty; Prakruthi, Hanumanthappagari; Sruthi, Thalla; Gowd, Mulinti Rajashekhar Gari Bhuthe; Haseena, Bogala; Babu, Niranjan (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Lamivudine is an Anti-Viral Drug belongs to BCS Class II Drug which exhibits limited solubility and high permeability through oral route. Aim The study was designed to predict the solubility potential of Lamivudine loaded Metal Organic Framework complexed with MIL 100 by using microwave assisted chemistry through topical route. Materials and Methods In combination of MIL 100 (Fe) we utilize Ferric chloride hexahydrate as metal particle and benzene 1,3,5-carboxyl corrosive as natural linker. The anti-viral drug Lamivudine was used to load in the MIL 100 (Fe). The specific proportion of FeCl3.6H2O and benzene 1,3,5-carboxylic acid was weakened with deionized water. Above combination is put in microwave at 130ºC for 6 min which prompts development of complex called MIL 100 (Fe). Various proportions of Lamivudine medication and MIL 100 (Fe) were taken to prepare the formulations and the effect of drug loading with various ratios were interpreted. Evaluation of MOF was done for drug-excipient compatibly studies and surface morphology for structural analysis. Results and Discussion Spectral studies conforms the purity of the sample and from drug-excipient compatibility studies no interactions were noticed. Microwave Assisted Technology can be proven as a best fit model for synthesis of advanced 2D Materials called MOF and drug loading was found to be high at a ratio of Lamivudine: MIL (1:0.5). The particulate studies conform the nanonisation of drug which results in enhanced solubility due to increased surface area of drugs. Conclusion Lamivudine loaded Metal Organic Frameworks (MOF) with MIL 100 (Fe) was successfully fabricated with high loading and decreased particle size authenticates the utilization of microwave assisted technology as a promising tool for MOF and with the result of increase in solubility, Lamivudine can be used in a best way as an anti-viral drug in the form of MOF through topical route.
Keywords: Metal Organic Frameworks; Ferric chloride hexahydrate; Benzene 1,3,5-tricarboxylic acid; Microwave assisted chemistry